2012
DOI: 10.1002/ffj.3099
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptor modulation by the volatile fractions of Sideritis species used as ‘Greek’ or ‘Turkish’ mountain tea

Abstract: Sideritis spp. is a member of the Labiateae family, used in traditional folk medicine and as a calming tea preparation. Dichloromethane extracts of the aerial parts of four Sideritis species were prepared, and the volatile fractions were separated via solvent‐assisted flavour evaporation distillation. In vitro electrophysiological techniques were used to investigate the physiological effects of these aroma extracts on ionotropic γ‐aminobutyric acid receptors (GABAA) in comparison to extracts of Lavandula spp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 38 publications
2
19
0
1
Order By: Relevance
“…Various nonvolatile compounds were identified that may account for the observed effects 18 . Moreover, it was shown that the volatile fraction of Sideritis extracts modulates α1β2 and α1β2γ2 GABA A R subtypes 3 , 18 . Therefore, the action of the VOCs present in Sideritis extracts on GABA A R may be a distinct part of the underlying mechanism for a sedative action of such tea preparations in addition to effects of nonvolatile compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Various nonvolatile compounds were identified that may account for the observed effects 18 . Moreover, it was shown that the volatile fraction of Sideritis extracts modulates α1β2 and α1β2γ2 GABA A R subtypes 3 , 18 . Therefore, the action of the VOCs present in Sideritis extracts on GABA A R may be a distinct part of the underlying mechanism for a sedative action of such tea preparations in addition to effects of nonvolatile compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Aroma compounds have been shown to modulate different types of receptors beyond the olfactory system, such as the γ-aminobutanoic acid (GABA A )-receptor [17,18] and the vanilloid transient receptor potential cation channel (TRPV1)-receptor [19]. Potential physiological effects in relation to food or beverages are often investigated on substances that occur naturally in the product, but potential metabolism within the body is rarely considered.…”
Section: Introductionmentioning
confidence: 99%
“…A range of such studies has been carried out and has demonstrated the mentioned effects in in vitro assays, e.g., in cell models functionally expressing specific receptors, ion channels or other physiological entities [25][26][27]. Amongst others, studies have demonstrated that odorants do not only act on metabotropic (i.e., G-protein coupled) receptors, but may also activate ionotropic pathways [28] (i.e., via ion channels); these modes of action are increasingly being discussed in the context of neurotropic action of odorants, such as in the CNS.…”
Section: Physiological Actionmentioning
confidence: 98%